Direct C-N bond formation in an in situ ligand transformation reaction and formation of polymeric 1D cadmium(II) complexes with end-to-end bridging thiocyanate or selenocyanate ions: Synthesis, structures and theoretical studies - Sadhu, Mehul H.; Solanki, Ankita; Kundu, T.; Hingu, Vinayak; Ganguly, B.; Kumar, Sujit B. (Polyhedron, 2017)
Two new one-dimensional polymeric thiocyanato and selenocyanato bridged cadmium(II) complexes [Cd(dpip)(mu(1,3)-SCN)(2)](n) and [Cd(dpip)(mu(1,3)-SeCN)(2)](n), where dpip = 3,5-dimethy1-14(3-phenylimidazolidin-ly1)-methyl)-1H-pyrazole have been synthesized and characterized by elemental analysis, IR, 1H NMR and single crystal X-ray diffraction studies. The bidentate N-2-coordinated ligand dpip is formed from N-4-coor-dinated tetradentate ligand N,N-bis(3,5-dimethy1-1H-pyrazol-1-yOmethyl-N-2-phenylethane-1,2-diamine (bdpab) due to unusual transformation, removing one pyrazole group and formation of saturated imidazole ring during in situ complexation reaction. The 1D structures of the two complexes have been confirmed by single crystal X-ray diffraction studies and both NCS- and NCSe- act as end -to -end (-1,3) bridging ligands. The coordination environment around the cadmium center in the complexes are CdN4S2 and CdN4Se2, respectively and each cadmium(II) center has distorted octahedral geometry. The distortion in the molecules are due to two unequal Cd-N (organic ligand dpip) bond lengths and small bite angel of the unsymmetrical organic ligand. The DFT calculations performed with cadmium(II) complexes [Cd (dpip)(mu(1,3)-SCN)(2)](n) and [Cd(dpip)(mu(1,3)-SeCN)(2)](n) corroborated the observed crystal structures and the structural parameter were found to be in good agreement in both calculated and X-ray geometries. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: 1d Chain; Cd(Ii) Complexes; Cobalt(Ii); coordination polymers; Crystal-structure; Dft Pyrazole Based Ligand; Dinuclear; End-to-end Bridge; Infrared-spectra; Magnetic-properties; Metal; Ncs/Secn Ion; Nickel(Ii); Nitrogen Single Bond